PHYSIOLOGICAL AND PATHOLOGICAL QUALITIES OF SOYBEAN SEEDS AFTER FUNGICIDE TREATMENT AND STORAGE UNDER DIFFERENT ENVIRONMENTS - ESTEVÃO, Carla Pereira (Scientia Agraria, 2002)
Soybean seeds [Glycine max (L.) Merrill] deteriorate rapidly under adverse storage conditions, especially under high temperatures and relative humidities. The present work, conducted at the National Center for Soybean Research Embrapa Soybean, Londrina/ PR had as objective to evaluate the physiological and pathological seed qualities of two cultivars of soybean (BRS 155 and Embrapa 48), treated or not with the fungicide carbendazin (30g a.i./100 kg of seed), stored in two ambient conditions: laboratory (open storage) and simulated tropical conditions (camera set to 25ºC/85% relative humidity) during a period of 180 days. The experimental design was a randomized complete block with four replications of 200 seeds, except in the tetrazolium test where 100 seeds were used by replication (two sub-samples of 50 seeds). To make the seed quality evaluations, the samples seed were collected every 30 days and submitted the following evaluations: determination of the seed moisture content, tetrazolium test, accelerated aging test, germination, seed health test (Blotter test) and emergence in sand. It was observed that there was no advantage of using the fungicide to prevent seed deterioration during storage. Seeds of both cultivars lost viability and vigor, after 120 days of storage under simulated tropical conditions (STC). Even so, seeds stored under laboratory conditions (open storage) maintained their quality along the storage period.